Structural analysis of the protein phosphatase 1 docking motif: Molecular description of the binding specificity identifies new ligands. - Meiselbach, Heike; Sticht, Heinrich; Enz, Ralf (Chemistry & Biology, 2006)
The interplay between kinases and phosphatases represents a fundamental regulatory mechanism in biological systems. Being less numerous than kinases, phosphatases increase their diversity by the acquisition of a variety of binding partners, thereby forming a large number of holoenzymes. Proteins interacting with protein phosphatase 1 (PP1) often bind via a so-called docking motif to regulate its enzymatic activity, substrate specificity, and subcellular localization. Here, we systematically determined structural elements that mediate the binding specificity of PP1 interacting proteins, and propose a refined consensus sequence for high-affinity PP1 ligands. Applying this pattern to database searches, we predicted and experimentally confirmed several previously unknown PP1 interactors. Thus, the suggested PP1 docking motif enables a highly specific prediction of PP1 binding partners, thereby facilitating the genome-wide identification of PP1 interactors.<br
UnivIS-Import:2015-04-14:Pub.2006.med.IB.profes_1.struct